Hubungan antara Dukungan Orang Tua dan Guru dengan Prestasi Belajar Geografi Siswa Kelas X di MA Ma’arif Udanawu Blitar - Dinda Bharotut Taqiyah; Yudi Krisno Wicaksono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The purpose of this study was to examine the relationship between parental and teacher support with geography learning achievement of grade X students at MA Ma'arif Udanawu Blitar. This research uses quantitative research and the type of correlation and relationship research. Data collection methods for parental and teacher support in this study using a questionnaire, while to obtain learning outcomes data using odd semester report card scores. This study used a sample of 96 students from a total population of 642 grade X students at MA Ma'arif Udanawu Blitar. Analysis data on hypothesis testing using product moment correlation test and multiple linear regression test. The results of this study indicate that parental support and teachers have a positive and significant relationship with geography learning achievement of grade X students at MA Ma'arif Udanawu Blitar, as evidenced by the significance value of the F test of 0.000 <0.05 then H0 is rejected and H1 is accepted.